Policy in The Implementation of Elementary and Junior High School Education Service in Medan - Zoraya Alfathin Rangkuti; M. Ridwan Rangkuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This article explains the importance of policy in public services in the city of Medan. The research method used is a descriptive qualitative approach with a case study approach. The politics of policy in the context of services in the field of education can be seen from the political processes, regulations, and education service systems that run from the process of admitting new students to the teaching and learning process. Education policy is the backbone of accelerating the improvement of human resources, especially in Medan City. In the context of education services, extortion in the administrative education process occurs extortion because of the inconsistency of existing regulations (regulations) and implemented (bureaucracy). This is evidenced by the practice of money administration at every level of student equipment at the elementary and middle school level. Policy politics related to education services encourage bureaucracy which has been rigid and corrupt so far to be dissolved in their existence in an adaptive public service administration system that is sustainable between government administrators and the community. Therefore, service-oriented policy politics in the education sector is an absolute and realistic policy for investing in quality human resources in the city of Medan as a manifestation of the constitutional mandate.